THE EFFECT OF FOOD QUALITY, PRICE, LIVE STREAMING AND SOCIAL MEDIA ON PURCHASING DECISIONS BAKSO SPICY CUB. JEMBER - Andini, Intan Nur; Hermawan, Haris; Setianingsih, Wahyu Eko (Jurnal Comparative: Ekonomi dan Bisnis, 2025)
This research aims to determine and analyze the influence of food quality, price, live streaming and Instagram social media on purchasing decisions for spicy meatballs in Kab. jember. The location of this research is Jl. Gajah Mada Gg. 14, RT.03/RW.14, Kaliwates, Jember Regency. This type of research uses quantitative methods with a sample size of 110 respondents and uses non-probability sampling techniques with purposive sampling techniques, using data collection techniques in the form of questionnaires to respondents. The data analysis technique for this research uses instrument testing, classical assumptions and multiple linear regression. The analysis results obtained show that food quality, price, live streaming and Instagram social media have a positive and significant influence, both partially and simultaneously, on purchasing decisions for Spycy meatballs in Jember Regency, with a contribution level of influence of 0.953 or 95%.